The IMF and the Crises in Greece, Ireland, and Portugal. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2016)
This volume book brings together nine background papers prepared for an evaluation by the IMF Independent Evaluation Office of 'the IMF and the crises in Greece, Ireland, and Portugal.' It presents an authoritative work on the evolving relationship between the IMF and the euro area, a common currency area founded in 1999 consisting of advanced, highly integrated economies in Europe. The euro area, or any common currency area for that matter, has posed challenges to the IMF's operational activities as its Articles of Agreement contain no provision for joint membership. The challenges became intense when a series of crises erupted in Greece, Ireland, and Portugal from 2009 to 2011, and the Fund was called upon to help intervene by offering its financing and crisis management expertise. The IMF found itself in uncharted territory where there was no precedent or established procedure. The chapters, many of which are prepared by prominent academics and former senior IMF officials who are thoroughly familiar with internal procedures, discuss various aspects of the IMF's engagement with the euro area, including precrisis surveillance, how key decisions were made, how the IMF collaborated with European institutions, and how it designed and implemented its lending programs with the three crisis countries. The book gives prominence to governance-related issues, given the large voting share (of more than 20 percent) within the IMF of euro area members and the subsequent public perception that the IMF treated the euro area more favorably than it does developing and emerging market members. The approaches are both cross-cutting and country-based. Some chapters deal with issues related to the euro area as a whole, while others focus on how the Fund engaged with individual euro area countries. The book contains a statement on the IEO evaluation by the IMF Managing Director and a Summing Up of the Executive Board discussion held in July 2016.